Uma proposta de abordagem de matemática financeira no ensino fundamental - Prado, João Paulo Sanchez de Almeida (Universidade Federal de São Carlos, 2021)
In this work we present a suggestion of approach and teaching practice on topics in financial mathematics, such as percentage, centesimal ratio, percentage variation, simple interest and compound interest, to be applied in Elementary School, especially in the 9th year, using methodologies with technological resources. The main objective of this work is to show that it is possible to enrich the teaching-learning process of Financial Mathematics through didactic sequences that make use of active methodologies and interactions mediated by simple and free technologies. As an end product of this work, we offer an activity proposal entitled "Vendendo Brigadeiros" and two didactic sequence suggestions that are "Aprendendo com planilhas eletrônicas" and "Aprendendo com a plaforma Scratch".
A proposal for a financial mathematics approach in fundamental education
Keywords: Matemática financeira; Sequência didática; Ensino fundamental; Financial math; Didatic sequence; Elementary school; CIENCIAS EXATAS E DA TERRA::MATEMATICA::ALGEBRA